Far-ultraviolet spectra of broad absorption line QSOs and constraints on models for the ionization structure and metallicity of the BAL-region gas - ESPEY, BRIAN RUSSELL (American Astronomical Society, 1996)
Hubble Space Telescope Faint Object Spectrograph G270H spectra of four moderate-to high-redshift broad absorption line (BAL) QSOs are presented. In addition, evidence is discussed that indicates that the gas that gives rise to the BALs has nonuniform ionization and enhanced abundances. In the context of a photoionization model, ionization parameter fluctuations of at least ~32-16 are needed to explain the observed column densities of different ions of the same element. In such a model, the gas must have very enhanced metal-to-hydrogen abundances relative to solar composition. However, the actual metal-to-hydrogen abundance enhancements are difficult to constrain because they are so model-dependent. For example, in a photoionization model the shape of the photoionizing continuum has a significant influence on the derived metal-to-hydrogen enhancement, but for normally adopted shapes the enhancement is very large, i.e., an enhancement of ~120-230 times solar for nitrogen. If collisional ionization is important, the need for metal-to-hydrogen abundance enhancements would be severely reduced. The derived relative metal abundances are somewhat more robust because the relevant metal-line transitions correspond to similar ionization potentials. In a photoionization model, nitrogen enhancements relative to oxygen and carbon of ~4-3 and 9:-10: times solar values, respectively, are indicated. If normal stellar nucleosynthesis is important, the results may be indicative of star formation with a relatively flat initial mass function, with the nitrogen overabundance produced by secondary processing in massive stars. However, large enhancements of elements like phosphorus in some objects suggest that the enrichment scenario may be more complex. In addition, the results discussed here place constraints on the details of a photoionization model for the BAL-region gas. These constraints are unphysical enough that they may indicate that central- source photoionization is not dominant.
PUBLISHED
Keywords: Physics